Peningkatan Minat Baca Siswa Melalui Penerapan Pembelajaran Berbasis Digital Storytelling di SDN 3 Ledok Kabupaten Blora - Tirta Puja Astuti; Susanti; Karjo (Impact: Jurnal Pengabdian kepada Masyarakat, 2024)
The advancement of digital technology has significantly influenced the learning patterns of the younger generation. However, reading interest among elementary school students remains relatively low and requires innovative approaches. This community service activity aimed to enhance students' reading interest through the implementation of digital storytelling-based learning at SDN 3 Ledok, Sambong District, Blora Regency. The program was carried out through training, mentoring, and hands-on practice in creating and utilizing digital storytelling media by teachers and students. The results of the activity showed an increase in student engagement in reading, discussing, and confidently retelling story content. This initiative also had a positive impact on students’ basic literacy skills and improved teachers' capacity to deliver enjoyable and meaningful learning experiences. Digital storytelling has proven to